Efforts to Increase Children's Reading Interest through the One-Shirt Education Program in Desa Sucenjurutengah Kecamatan Bayan Kabupaten Purworejo - Aryanto, Aris; Fikrul Haq, Hasbi; At Thooriq, Dzikri (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
The Baju Satu Education Program is held every Friday and Saturday which is attended by kindergarten and elementary school children in grades 1-6. This activity is carried out every Friday and Saturday at 14.00 WIB. The Baju Satu education program is carried out to increase interest in learning, especially reading. The method used in Baju Satu learning is the play method. Learning titled Baju Satu is focused on the process of learning to read and reading comprehension. The media used are reading books, props, and also interspersed with listening to movies. Assessment or evaluation is carried out every time the activity is completed. The assessment is carried out by the student on duty based on several criteria, including attendance, activeness, intelligence, responsibility, and manners. At the last meeting, gifts were given to the children as a form of appreciation for learning